Viruses and Protists Induced-mortality of Prokaryotes around the Antarctic Peninsula during the Austral Summer - Vaqué, Dolors; Boras, Julia A.; Torrent-Llagostera, Francesc; Agustí, Susana; Arrieta, Jesús M.; Lara, Elena; Castillo, Yaiza M.; Duarte, Carlos M.; Sala, Maria M. (Frontiers in Microbiology, 2017)
During the Austral summer 2009 we studied three areas surrounding the Antarctic Peninsula: the Bellingshausen Sea, the Bransfield Strait and the Weddell Sea. We aimed to investigate, whether viruses or protists were the main agents inducing prokaryotic mortality rates, and the sensitivity to temperature of prokaryotic heterotrophic production and mortality based on the activation energy (Ea) for each process. Seawater samples were taken at seven depths (0.1-100 m) to quantify viruses, prokaryotes and protists abundances, and heterotrophic prokaryotic production (PHP). Viral lytic production, lysogeny, and mortality rates of prokaryotes due to viruses and protists were estimated at surface (0.1-1m) and at the Deep Fluorescence Maximum (DFM, 12-55 m) at eight representative stations of the three areas. The average viral lytic production ranged from 1.0±0.3*107 viruses ml-1 d-1 in Bellingshausen Sea to1.3±0.7*107 viruses ml-1 d-1 in the Bransfield Strait, while lysogeny, when detectable, recorded the lowest value in Bellingshausen Sea (0.05±0.05*107 viruses ml-1 d-1) and the highest in the Weddell Sea (4.3±3.5*107 viruses ml-1 d-1). Average mortality rates due to viruses ranged from 9.7±6.1*104 cells ml-1 d-1 in the Weddell Sea to 14.3±4.0*104 cells ml-1 d-1 in the Bellingshausen Sea, and were higher than averaged grazing rates in the Weddell Sea (5.9±1.1*104 cells ml-1 d-1) and in the Bellingshausen Sea (6.8±0.9*104 cells ml-1 d-1). The highest impact on prokaryotes by viruses and main differences between viral and protists activities were observed in surface samples: 17.8±6.8*104 cells ml-1 d-1 and 6.5±3.9*104 cells ml-1 d-1 in the Weddell Sea; 22.1±9.6 *104 cells ml-1 d-1 and 11.6±1.4 *104 cells ml-1 d-1 in the Bransfield Strait; and 16.1±5.7*104 cells ml-1 d-1 and 7.9±2.6*104 cells ml-1 d-1 in the Bellingshausen Sea, respectively. Furthermore, the rate of lysed cells and PHP showed higher sensitivity to temperature than grazing rates by protists. We conclude that viruses were more important mortality agents than protists mainly in surface waters and that viral activity has a higher sensitivity to temperature than grazing rates. This suggests a reduction of the carbon transferred through the microbial food-web that could have implications in the biogeochemical cycles in a future warmer ocean scenario.